(untitled) (University Heart Journal, 2009)
Despite of modern medical treatment heart failure patients suffer frequently. The optimization of medical therapy is an emphasis for these patients. Device therapy has been showed some improvement in prognosis but nonresponder rate is still 30% in many large trails. So, selection of patients for devices is important as these are expensive. Optimization of medical treatment is the priority and device can be used as an additional option. doi: 10.3329/uhj.v5i1.3439 University Heart Journal Vol. 5, No. 1, January 2009 32-35